4(2x-8)-2=4(x-4)+6

Simple and best practice solution for 4(2x-8)-2=4(x-4)+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-8)-2=4(x-4)+6 equation:


Simplifying
4(2x + -8) + -2 = 4(x + -4) + 6

Reorder the terms:
4(-8 + 2x) + -2 = 4(x + -4) + 6
(-8 * 4 + 2x * 4) + -2 = 4(x + -4) + 6
(-32 + 8x) + -2 = 4(x + -4) + 6

Reorder the terms:
-32 + -2 + 8x = 4(x + -4) + 6

Combine like terms: -32 + -2 = -34
-34 + 8x = 4(x + -4) + 6

Reorder the terms:
-34 + 8x = 4(-4 + x) + 6
-34 + 8x = (-4 * 4 + x * 4) + 6
-34 + 8x = (-16 + 4x) + 6

Reorder the terms:
-34 + 8x = -16 + 6 + 4x

Combine like terms: -16 + 6 = -10
-34 + 8x = -10 + 4x

Solving
-34 + 8x = -10 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-34 + 8x + -4x = -10 + 4x + -4x

Combine like terms: 8x + -4x = 4x
-34 + 4x = -10 + 4x + -4x

Combine like terms: 4x + -4x = 0
-34 + 4x = -10 + 0
-34 + 4x = -10

Add '34' to each side of the equation.
-34 + 34 + 4x = -10 + 34

Combine like terms: -34 + 34 = 0
0 + 4x = -10 + 34
4x = -10 + 34

Combine like terms: -10 + 34 = 24
4x = 24

Divide each side by '4'.
x = 6

Simplifying
x = 6

See similar equations:

| 2x+28=9x-28 | | 3(4x-1)=48 | | 0.4(x-4)=7.2 | | 4xy^4-32xy=0 | | -9(x-4)-3=46 | | 0.5x-0.1(5-x)=2.2 | | 77/121 | | -7-6=7-8x | | -3(2x+1)=21 | | 5(4x-3)=11 | | 4y^3+12y^2+5y=0 | | 23=49-7x | | f(x)=x^3-2x^2+2x-6 | | 20-9w=4(15-1w) | | 11+9lnx=6 | | y+11=19 | | 9p+-5=1 | | 5x=81.2 | | 2x^2=-5x-10 | | z^(-3)/z^(-7) | | 87=2x-3(5x-3) | | -4(-2+2x)=-32 | | (9m-15)6=18 | | x^2-2x-15/6x^2-54 | | 5x^2+7x=4 | | -4(-4-6x)=88 | | 3x-8=58-2x | | 3(4x-1)-7x=16 | | 5x+26+14x=82 | | 2x^2+8=32 | | 3^(-4)/3 | | 32-3x=6x+21 |

Equations solver categories